Wood Vault: remove atmospheric CO2 with trees, store wood for carbon sequestration for now and as biomass, bioenergy and carbon reserve for the future - Zeng, Ning; Hausmann, Henry (Carbon balance and management, 2022)
Background Wood harvesting and storage (WHS) is a hybrid Nature-Engineering combination method to combat climate change by harvesting wood sustainably and storing it semi-permanently for carbon sequestration. To date, the technology has only been purposefully tested in small-scale demonstration projects. This study aims to develop a concrete way to carry out WHS at large-scale. Results We describe a method of constructing a wood storage facility, named Wood Vault, that can bury woody biomass on a mega-tonne scale in specially engineered enclosures to ensure anaerobic environments, thus preventing wood decay. The buried wood enters a quasi-geological reservoir that is expected to stay intact semi-permanently. Storing wood in many environments is possible, leading to seven versions of Wood Vault: (1) Burial Mound (Tumulus or Barrow), (2) Underground (Pit, Quarry, or Mine), (3) Super Vault, (4) Shelter, (5) AquaOpen or AquaVault with wood submerged under water, (6) DesertOpen or DesertVault in dry regions, (7) FreezeVault in cold regions such as Antarctica. Smaller sizes are also possible, named Baby Vault. A prototype Wood Vault Unit (WVU) occupies 1 hectare (ha, 100 m by 100 m) of surface land, 20 m tall, stores up to 100,000 m 3 of wood, sequestering 0.1 MtCO 2 . A 1 MtCO 2 y −1 sequestration rate can be achieved by collecting currently unused wood residuals (WR) on an area of 25,000 km 2 , the size of 10 typical counties in the eastern US, corresponding to an average transportation distance of less than 100 km. After 30 years of operation, such a Wood Vault facility would have sequestered 30 MtCO 2 , stored in 300 WVUs, occupying a land surface of 300 ha. The cost is estimated at $10–50/tCO 2 with a mid-point price of $30/tCO 2 . To sequester 1 GtCO 2 y −1 , wood can be sourced from currently unexploited wood residuals on an area of 9 Mkm 2 forested land (9 million square kilometers, size of the US), corresponding to a low areal harvesting intensity of 1.1 tCO 2 ha −1 y −1 . Alternatively, giga-tonne scale carbon removal can be achieved by harvesting wood at a medium harvesting intensity of 4 tCO 2 ha −1 y −1 on 3 Mkm 2 of forest (equivalent to increasing current world wood harvest rate by 25%), or harvest on 0.8 Mkm 2 forest restored from past Amazon deforestation at high harvest intensity, or many combinations of these and other possibilities. It takes 1000 facilities as discussed above to store 1 GtCO 2 y −1 , compared to more than 6000 landfills currently in operation in the US. After full closure of a Wood Vault, the land can be utilized for recreation, agriculture, solar farm, or agrivoltaics. A more distributed small operator model (Baby Vault) has somewhat different operation and economic constraints. A 10 giga-tonne sequestration rate siphons off only 5% of total terrestrial net primary production, thus possible with WHS, but extreme caution needs to be taken to ensure sustainable wood sourcing. Conclusions Our technical and economic analysis shows that Wood Vault can be a powerful tool to sequester carbon reliably, using a variety of wood sources. Most pieces of the technology already exist, but they need to be put together efficiently in practice. Some uncertainties need to be addressed, including how durability of buried wood depends on detailed storage methods and burial environment, but the science and technology are known well enough to believe the practicality of the method. The high durability, verifiability and low-cost makes it already an attractive option in the current global carbon market. Woody biomass stored in Wood Vaults is not only a carbon sink to combat current climate crisis, but also a valuable resource for the future that can be used as biomass/bioenergy and carbon supply. The quantity of this wood utilization can be controlled carefully to maintain a desired amount of CO 2 in the atmosphere to keep the Earth’s climate from diving into the next ice age, acting as a climate thermostat. The CO 2 drawdown time is on the order of 100 years while the ramp-up time is a decade. A sense of urgency is warranted because the CO 2 removal rate is limited by biosphere productivity, thus delayed action means a loss of opportunity. In conclusion, WHS provides a tool for managing our Earth system, which will likely remain forever in the Anthropocene.